2021
DOI: 10.1021/acssuschemeng.1c01155
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Few-Layer Ti3C2 MXene and Boron-Doped g-C3N4 for Enhanced Photocatalytic CO2 Reduction

Abstract: The conversion of carbon dioxide (CO2) into high-value-added chemicals by photocatalysis is recognized as a potential method to ease the greenhouse effect and the global energy crisis simultaneously. Herein, boron-doped graphitic carbon nitride (g-C3N4) was combined with few-layer Ti3C2 MXene (FLTC) by electrostatic self-assembly. The composite exhibited superior performance to bare g-C3N4 and B-doped g-C3N4 (BCN). The optimized 12FLTC/BCN produced 3.2- and 8.9-times higher CO and CH4 yields, respectively, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 65 publications
(103 reference statements)
0
32
0
Order By: Relevance
“…11,12 Photocatalytic N 2 fixation over g-C 3 N 4 has been proven to be theoretically feasible, 13 nevertheless, bulk g-C 3 N 4 usually suffers from severe recombination of photogenerated electron–hole pairs and poor transfer rate of charge carriers, resulting in low N 2 photofixation efficiency. 14,15 In principle, N 2 photofixation is a multi-charge transfer process, which requires the accumulation of multiple electrons on the N 2 adsorption sites of the photocatalyst. Therefore, it is essential to conquer the critical issues of poor charge carrier separation efficiency and transfer rate to realize highly effective N 2 photofixation on g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Photocatalytic N 2 fixation over g-C 3 N 4 has been proven to be theoretically feasible, 13 nevertheless, bulk g-C 3 N 4 usually suffers from severe recombination of photogenerated electron–hole pairs and poor transfer rate of charge carriers, resulting in low N 2 photofixation efficiency. 14,15 In principle, N 2 photofixation is a multi-charge transfer process, which requires the accumulation of multiple electrons on the N 2 adsorption sites of the photocatalyst. Therefore, it is essential to conquer the critical issues of poor charge carrier separation efficiency and transfer rate to realize highly effective N 2 photofixation on g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry (MS) was performed using an electrospray ionization quadrupole time-of-flight mass spectrometer (ESI-QTOF MS, Dionex Mate 3000). 1 H NMR spectra were recorded by the AVANCE III 400 MHz instrument. Scanning electron microscope (SEM) image was collected on a Quanta 400FEG microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The greenhouse effect has caused global temperatures to rise, resulting in rising sea levels and more extreme weather. Excessive accumulation of CO 2 has caused the greenhouse effect [1][2][3][4]. At present, controlling CO 2 emissions, effectively converting excess CO 2 , and establishing a healthy carbon cycle are common problems faced by mankind.…”
Section: Introductionmentioning
confidence: 99%
“…It has confirmed that the role of MXene with excellent electronic conductivity boosts the separation and migration of the photoinduced carriers. [ 164 ] These few reported works have demonstrated the diverse use of MXene cocatalysts in enhancing 2D g‐C 3 N 4 based semiconductors in numerous photocatalytic applications.…”
Section: G‐c3n4 Based Photocatalysts With 2d Cocatalysts and Their Ap...mentioning
confidence: 99%